2019
DOI: 10.1111/cpr.12572
|View full text |Cite
|
Sign up to set email alerts
|

Advances of tooth‐derived stem cells in neural diseases treatments and nerve tissue regeneration

Abstract: Nerous system diseases, both central and peripheral, bring an incredible burden onto patients and enormously reduce their quality of life. Currently, there are still no effective treatments to repair nerve lesions that do not have side effects. Stem cellbased therapies, especially those using dental stem cells, bring new hope to neural diseases. Dental stem cells, derived from the neural crest, have many characteristics that are similar to neural cells, indicating that they can be an ideal source of cells for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 111 publications
(349 reference statements)
0
43
0
Order By: Relevance
“…The application of combined DSCs with various scaffolds promotes the function of injured neural tissues and reduces the inflammatory responses. The most common scaffolds applied for neural tissue regeneration and repair include chitosan, heparin-poloxamer, silicone tubes, poly-ε-caprolactone/poly-lactide-co-glycolic acid, and electrospun neuro-supportive scaffolds[ 191 ]. Different scaffolds were used to enhance neural differentiation and promote their neuronal characteristics.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…The application of combined DSCs with various scaffolds promotes the function of injured neural tissues and reduces the inflammatory responses. The most common scaffolds applied for neural tissue regeneration and repair include chitosan, heparin-poloxamer, silicone tubes, poly-ε-caprolactone/poly-lactide-co-glycolic acid, and electrospun neuro-supportive scaffolds[ 191 ]. Different scaffolds were used to enhance neural differentiation and promote their neuronal characteristics.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…DPSCs are positive for STRO-1, CD146, CD73, and CD90. Similar to other MSCs, DPSCs are capable of multilineage differentiation, including osteogenesis, chondrogenesis, adipogenesis, and myogenic lineages[ 9 - 15 ]. Regarding neural differentiation, DPSCs have a higher positive ratio for neural markers such as Nestin, GFAP, and s100-beta than other kinds of MSCs[ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dental MSCs have been suggested to promote taste bud regeneration and have promising potential applications in postsurgery tongue reconstruction of patients with tongue cancer [ 106 ]. Interestingly, recent work has also suggested that SHEDs exert a protective effect on the secretory function of the salivary gland and exhibit therapeutic potential for the improvement of hyposalivation in Sjogren's syndrome [ 107 ].…”
Section: Dental Msc-based Therapy For Nondental Diseasesmentioning
confidence: 99%
“…Other dental MSCs have also been applied in the treatment of extraoral diseases like neurodegenerative diseases and autoimmune and orthopedic disorders. Dental MSCs have a remarkable potential to treat neural diseases such as spinal cord injury (SCI) and peripheral nerve injury, like sciatic nerve and superior laryngeal nerve (SLN) injury, owing to their ability to differentiate into neural-like cells and regenerate neural tissue [ 107 ]. SCI is a severe traumatic central nervous system disease resulting in the damage of sensory and motor functions.…”
Section: Dental Msc-based Therapy For Nondental Diseasesmentioning
confidence: 99%